2018
DOI: 10.1017/s0031182018001786
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic resistance and novel control options in equine gastrointestinal nematodes

Abstract: Control of equine nematodes has relied on benzimidazoles (BZs), tetrahydropyrimidines and macrocyclic lactones. The intensive use of anthelmintics has led to the development of anthelmintic resistance (AR) in equine cyathostomins and Parascaris equorum. Field studies indicate that BZ and pyrantel resistance is widespread in cyathostomins and there are also increasing reports of resistance to macrocyclic lactones in cyathostomins and P. equorum. The unavailability of reliable laboratory-based techniques for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 155 publications
0
48
0
Order By: Relevance
“…could expand this population. While viral exposure burdens are likely to be largely similar to burdens experienced by humans, horses in the northeastern U.S. are also frequently exposed to Borrelia burgdorferi (agent of Lyme disease) (69) and Sarcocystis neurona (agent of Equine protozoal myeloencephalitis) (70), and are continuously infested with or re-exposed to gastrointestinal nematodes (71). The horses in this study did not show signs of active infection or inflammation, as they all had normal complete blood count, serum amyloid A, iron indices, and globulins.…”
Section: Discussionmentioning
confidence: 99%
“…could expand this population. While viral exposure burdens are likely to be largely similar to burdens experienced by humans, horses in the northeastern U.S. are also frequently exposed to Borrelia burgdorferi (agent of Lyme disease) (69) and Sarcocystis neurona (agent of Equine protozoal myeloencephalitis) (70), and are continuously infested with or re-exposed to gastrointestinal nematodes (71). The horses in this study did not show signs of active infection or inflammation, as they all had normal complete blood count, serum amyloid A, iron indices, and globulins.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations are that a FECRT be performed each year to avoid using ineffective anthelmintics (Tzelos and Matthews, 2016). Going forward, considering the levels of anthelmintic resistance reported in cyathostomins and in P. equorum (Raza et al, 2019), improved knowledge transfer from prescribers to horse owners needs to highlight the benefit of efficacy testing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Queensland has demonstrated that the 95% inhibitory concentration (IC95) is a more consistent measure of the larval response than the IC50 in the larval migration inhibition test (in a 96 well format) for the detection of ML-resistant cyathostomins [76]. A number of studies have shown promising results from in vitro methods used in ruminants for the estimation of anthelmintic sensitivity and AR, but further studies are required to evaluate the usefulness of these methods in horses [88, 96, 97].…”
Section: Control Of Gins In Horsesmentioning
confidence: 99%